Optimal Placement of Shunt Capacitor in Distribution System by Particle Swarm Optimization - Ahmed, Shahzor; Kumar, Mahesh; Soomro, Amir Mahmood (International Journal of Integrated Engineering, 2020)
In Pakistan the distribution system, have power loss and voltage drop issues due to outdated infrastructure. As the load used in distribution side is mostly inductive so there are reactive power losses issues. Therefore, an attempt is made to integrate shunt capacitor banks to improve reactive power losses and to maintain the voltage profile in the allowable limit. Moreover, one of the 11kV distribution feeders of Hyderabad is selected for analysis of reactive power loss issue caused due to reactive loads. An artificial intelligence technique named as particle swarm optimization (PSO) is used to identify the optimal placement of shunt capacitor. The proposed technique results are very effective for reduction in reactive power loss and voltage drop with fast convergence.